GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

It is currently 07 Aug 2020, 01:23

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 65841
If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of  [#permalink]

Show Tags

New post 23 Jun 2020, 02:55
00:00
A
B
C
D
E

Difficulty:

  35% (medium)

Question Stats:

73% (01:53) correct 27% (01:16) wrong based on 26 sessions

HideShow timer Statistics

GMAT Tutor
avatar
P
Joined: 24 Jun 2008
Posts: 2397
Re: If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of  [#permalink]

Show Tags

New post 23 Jun 2020, 04:11
1
By substitution,

f(g(x)) = f(4-x) = 2(4 - x) - 2 = 6 - 2x

and

g(f(x)) = g(2x - 2) = 4 - (2x - 2) = 6 - 2x

so f(g(x)) and g(f(x)) are identical no matter what x is equal to.
_________________
GMAT Tutor in Montreal

If you are looking for online GMAT math tutoring, or if you are interested in buying my advanced Quant books and problem sets, please contact me at ianstewartgmat at gmail.com
Senior Manager
Senior Manager
User avatar
G
Joined: 14 Aug 2019
Posts: 329
Location: India
Concentration: Marketing, Finance
Re: If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of  [#permalink]

Show Tags

New post 23 Jun 2020, 04:16
fgx means = 2( 4-x) -2= 8-2x-2= 6-2x
gfx means = 4-(2x-2)= 4-2x+2= 6-2x

as both are same factors
then any value of x should result in fgx = gfx

hence option E
PS Forum Moderator
User avatar
P
Joined: 18 Jan 2020
Posts: 1547
Location: India
GPA: 4
Premium Member CAT Tests
Re: If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of  [#permalink]

Show Tags

New post 23 Jun 2020, 05:04
1
F(x) = 2x-2
G(x) = 4-x

F(G(x)) = G(F(x))
F(4-x) = G(2x-2)
2(4-x)-2 = 4-2x+2
8-2x-2 = 6-2x
6-2x = 6-2x

So, irrespective of any value, integer or not. F(G(x)) will always be equal to G(F(x))

Answer is E

Posted from my mobile device
GMAT Club Bot
Re: If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of   [#permalink] 23 Jun 2020, 05:04

If f(x) = 2x - 2 and g(x) = 4 - x, then f(g(x)) = g(f(x)) for which of

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





cron

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne